Factors Affecting the Return Stock Company in Indonesia Stock Exchange (IDX) LQ45 in Years 2012-2015 - Fangki A. Sorongan (The Winners, 2016)
This research aimed to determine the effect of partially and jointly independent variable of Debt to Equity Ratio (DER), Return on Equity (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) against the dependent variable on the stock return. Objects of this research were companies listed on the Indonesia Stock Exchange (BEI) LQ45 continuously for four years in the period 2012-2015. Companies that qualify for this research were 28 companies. Based on this research, the conclusions indicate that all four independent variables; Debt to Equity Ratio (DER), Return on Equity (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), either jointly or partially give the significant effect on return stock.